Angiogenesis related genes NOS3, CD14, MMP3 and IL4R are associated to VEGF gene expression and circulating levels in healthy adults. Issue 1 (December 2015) - Saleh, Abdelsalam; Stathopoulou, Maria; Dadé, Sébastien; Ndiaye, Ndeye; Azimi-Nezhad, Mohsen; Murray, Helena; Masson, Christine; Lamont, John; Fitzgerald, Peter; Visvikis-Siest, Sophie
Abstract Background Vascular endothelial growth factor (VEGF) plays a key role in angiogenesis. The aim was to assess the genetic connections between the angiogenesis-relatedNOS3, CD14, MMP3, IL4R, IL4 genes and VEGF expression and plasma levels. Methods The associations between VEGF plasma levels with the polymorphisms ofNOS3, CD14, MMP3, IL4R, andIL4 were assessed in 403 healthy unrelated adults. The epistatic and environmental interactions were explored, including four VEGF-related polymorphisms previously identified. The VEGF expression in peripheral blood mononuclear cells was quantified (n = 65) for the VEGF121, VEGF145, VEGF165, and VEGF189 isoforms. Results The polymorphism rs1799983 ofNOS3 was associated with the sum of all VEGF isoforms mRNA levels (P = 0.032) and VEGF145 (P = 0.033). Rs1800779 ofNOS3 interacted with rs3918226 of the same gene and with the rs2569190 ofCD14 (P = 0.022, P = 0.042, respectively) for VEGF plasma levels. Other epistatic interactions included the rs1801275 ofIL4R with the rs6921438 (VEGF-related variant) and rs3025058 ofMMP3 (P = 0.042, P = 0.010 respectively) and the rs2569190 ofCD14 with the rs3025058 ofMMP3 (P = 0.0119). We also identified an interaction of rs1800779 with obesity, high-density lipoprotein cholesterol and triglycerides (P = 0.018, P = 0.005, P = 0.043, respectively) as well as the interaction of rs6921438 with hypertension (P = 0.028). Conclusions Our findings indicated that genetic variants ofNOS3, CD14, MMP3 andIL4R are implicated in the determination of VEGF expression and plasma levels. Thus, they support the hypothesis that in physiological conditions there are complex biological relationships between pathways (such as angiogenesis and inflammation), which are involved in the development of chronic diseases.